A nationalist network in South America: Diaspora and diplomatic action - Cruset, Maria Eugenia (2021)
The apparent failure of the Easter Rising in 1916 set off a chain of events that culminated in the creation of the Irish Free State in 1922. Considered by the Irish people as the martyrdom of their republican leaders, it served to continue the fi ght through other strategies, not restricted only to armed confl ict. Th e Sinn Féin began to coordinate a transnational political action network by means of its diaspora. Th is state of aff airs has been studied in cases such as the United States of America, Australia and Canada, but has not been delved into in the case of the countries of the Southern Cone – Paraguay, Uruguay, Argentina, Chile and southern Brazil. In this essay, I intend to analyse the role of immigrants in Argentina and their prominence in this strategy as well as how the network expanded through Chile and Uruguay.